Growth of Novel Ceramic Layers on Metals via Chemical and Heat Treatments for Inducing Various Biological Functions - Kokubo, Tadashi; Yamaguchi, Seiji (Frontiers in Bioengineering and Biotechnology, 2015)
The present authors’ systematic studies on growth of novel ceramic layers on Ti metal and its alloys by chemical and heat treatments for inducing bone-bonding bioactivity and some other biological functions are reviewed. Ti metal formed an apatite on its surface in a simulated body fluid (SBF), when heat-treated after exposure to strong acid solutions to form rutile surface layer, or to strong alkali solutions to form sodium titanate surface layer. Both types of Ti metal tightly bonded to the living bone. The alkali and heat treatment was applied to the surface Ti metal of an artificial hip joint and successfully used in the clinic since 2007. The acid and heat treatments was applied to porous Ti metal to induce osteoconductivity as well as osteoinductivity. The resulting product was successfully used in clinical trials for spinal fusion devices. For the Ti-based alloys, the alkali and heat treatment was a little modified to form calcium titanate surface layer. Bone-growth promoting Mg, Sr, and Zn ions as well as the antibacterial Ag ion were successfully incorporated into the calcium titanate layer.